Legal Standing of Condominium Owners Association Independently Established During Developer Bankruptcy - Rateh Nyimas Intan; H. Aslan Noor; Petra Bunawan (Magister Kenotariatan Universitas Pasundan, 2025)
This study examines the legal standing of condominium owners' association establishment deeds created independently by unit owners and residents when the developer company is declared bankrupt. The research also identifies appropriate dispute-resolution mechanisms for resolving disputes between residents and bankrupt developers regarding association formation. This study employs a normative juridical method, drawing on statutory and case law. Law Number 20 of 2011 concerning Condominiums mandates developers to establish owners' associations within a specified period. However, in practice, developers fail to fulfil this obligation, leaving residents without legal representation in collective property management. In such circumstances, unit owners may independently form their association through deliberation, documented in a notarial deed. The findings demonstrate that association establishment deeds created independently by residents possess valid legal standing and binding force, provided they satisfy the requirements under Article 1320 of the Indonesian Civil Code and comply with applicable procedural regulations. The developer's bankruptcy status does not invalidate a previously established association, as the association constitutes an independent legal entity separate from the developer. Dispute resolution should prioritise mediation to achieve mutual agreement among the parties. However, when mediation fails due to the developer's bad faith or unwillingness to transfer management authority, residents may file lawsuits to obtain legal certainty and compensation for damages incurred. Additionally, developers who neglect their obligation to facilitate association formation may be subject to administrative sanctions under condominium regulations.